Facts about Wildlife Diseases: SARS-CoV2 in white-tailed deer: WEC445/UW490, 1/2022 - Wisely, Samantha M (EDIS, 2022)
SARS Cov2, the virus that causes COVID-19, has been discovered in white-tailed deer. This publication provides information to the general public, hunters, and deer farmers as to what SARS CoV2 is, the evidence for COVID-19 in deer, and if people can get COVID-19 from deer.